Assessment of drug delivery devices working at microflow rates - Niemann, Anders Koustrup; Batista, Elsa; Geršl, Jan; Bissig, Hugo; Büker, Oliver; Lee, Seok Hwan; Graham, Emmelyn; Stolt, Krister; Afonso, Joana; Benková, Miroslava; Knotek, Stanislav (Biomedizinische Technik. Biomedical engineering, 2023)
Almost every medical department in hospitals around the world uses infusion devices to administer fluids, nutrition, and medications to patients to treat many different diseases and ailments. There have been several reports on adverse incidents caused by medication errors associated with infusion equipment. Such errors can result from malfunction or improper use, or even inaccuracy of the equipment, and can cause harm to patients' health. Depending on the intended use of the equipment, e.g. if it is used for anaesthesia of adults or for medical treatment of premature infants, the accuracy of the equipment may be more or less important. A well-defined metrological infrastructure can help to ensure that infusion devices function properly and are as accurate as needed for their use. However, establishing a metrological infrastructure requires adequate knowledge of the performance of infusion devices in use. This paper presents the results of various tests conducted with two types of devices.
Keywords: metrological infrastructure; microflow; Humans; calibration; Drug Delivery Systems; lidé; infusion device; lékové transportní systémy